ANALISIS PROBLEMATIKA KEBIJAKAN UPAH MINIMUM DAN TANTANGAN HUKUM DALAM INDUSTRI PERHOTELAN DI INDONESIA - Abrori; Fitri Melawati; Noviyanti; Surnadi (I’tiqadiah: Jurnal Hukum dan Ilmu-ilmu Kesyariahan, 2026)
The issue of minimum wage policy in Indonesia, particularly within the hospitality industry, remains a complex and ongoing debate. This policy plays a significant role in improving the welfare of workers; however, its implementation faces legal challenges and discrepancies between government regulations and practical realities. This study aims to analyze the problems associated with the minimum wage policy in the hospitality sector and the legal challenges faced by both workers and employers in its enforcement. The research employs a normative juridical approach using library research methods, including an examination of laws and regulations, related literature, and field data regarding the implementation of the minimum wage policy in the hospitality industry. The findings of the study reveal that although the minimum wage policy has been established to protect workers, its implementation remains uncertain. Legal challenges include the misalignment between the government-set minimum wage and the financial capacity of hotels, as well as differing interpretations of existing regulations. Additionally, there are practices of non-compliance by some employers, which adversely affect workers. The study recommends strengthening supervision of minimum wage implementation, simplifying regulations, and tightening sanctions for businesses that violate the rules in order to achieve social justice for workers in the hospitality sector.